Pembuatan Plang Edukasi Sampah Terurai di Desa Sarah Perlak Kecamatan Sungai Mas Kabupaten Aceh Barat - Mahmud Basuki; Andrean Riski Winanda; Ainul Hafifah; Faujiah Alya Sari Sagala; Santika Santika; Widyanti Salha; Melisa Rahayu; Muhammad Khairul; Muhammad Chairil; Arrazy Elba Ridha (Pusat Riset dan Inovasi Nasional, 2025)
Waste management remains a serious problem, particularly in rural areas, which generally have relatively low levels of environmental awareness. Inorganic waste such as plastic, glass, and aluminum is a major concern because it takes hundreds of years to decompose naturally. This situation poses potential long-term environmental hazards, including soil and water pollution, and ecosystem disruption. Therefore, effective educational efforts are needed to raise public awareness of waste issues. This community service activity was carried out in Sarah Perlak Village, Sungai Mas District, West Aceh Regency. The focus of the activity was the installation of educational signs containing information about the decomposition time of various types of waste. Implementation methods included direct observation to identify specific problems at the site, informal outreach to local residents, demonstrations related to waste sorting, and the creation and installation of educational signs. The signs were made from wooden planks and decorated with real waste such as plastic bottles, aluminum cans, and used paper, thus providing a tangible visualization to the community. The results of the activity showed that the visual approach through educational signs was able to attract the attention of residents, both children and adults. The information was presented clearly and accompanied by real-life examples, making the message easier to understand and remember. In addition, direct interaction through outreach and demonstrations provided an opportunity for residents to ask questions and share experiences related to waste management. Overall, this educational medium has proven effective in conveying environmental messages, raising awareness, and motivating the community to start sorting and reducing waste at the source. Going forward, this program is planned to be expanded through training in processing waste into useful products, thereby not only reducing pollution but also providing economic benefits to the community.